2017
DOI: 10.1016/j.brainres.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal onset as a critical transition for neural development and cognition

Abstract: Adolescence, broadly defined as the period between childhood and adulthood, is characterized by a variety of neuroanatomical and behavioral changes. In human adolescents, the cerebral cortex, especially the prefrontal cortex, decreases in size while the cortical white matter increases. Puberty appears to be an important factor in both of these changes. However, the white matter continues to grow beyond what is thought to be adolescence, while the grey matter of the cortex stabilizes by young adulthood. The siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 79 publications
9
135
0
Order By: Relevance
“…Studies examining plasma and brain levels of stimulants have found that adolescents have lower (Spear and Brake 1983;Kokoshka et al 2000;McCarthy et al 2004;Craig et al 2014), higher (Caster et al, 2005), or similar levels (McCarthy et al, 2004;Caster et al, 2005) compared to adults. Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g. dopamine transporter function; Volz et al, 2009) contribute to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining plasma and brain levels of stimulants have found that adolescents have lower (Spear and Brake 1983;Kokoshka et al 2000;McCarthy et al 2004;Craig et al 2014), higher (Caster et al, 2005), or similar levels (McCarthy et al, 2004;Caster et al, 2005) compared to adults. Based on the extensive changes occurring in the brain during adolescence (Andersen et al 1997(Andersen et al , 2000Dagher et al 2001;Koss et al 2014;Juraska and Willing 2017), another possibility is that differences in pharmacodynamics (e.g. dopamine transporter function; Volz et al, 2009) contribute to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence indicates that the medial prefrontal cortex exhibits age-dependent sexual dimorphism [38-40]. For example, there is a loss of volume during adolescence, which is at least partially attributable to a loss of neurons, which is more significant in females [41].…”
Section: Discussionmentioning
confidence: 99%
“…This emergent sexual dimorphism also appears to be driven by ovarian hormones because prepubertal GDX significantly increases white matter volume in females but does not affect white matter volume in males (Koss, et al, 2015). Thus, under normative developmental conditions, the emergence of sex differences in mPFC gray and white matter during adolescence in rats are due to the actions of ovarian, not testicular, hormones on cell death, synaptic pruning, and myelination (Juraska & Willing, 2016). The situation appears to be different for adolescent development of white matter in humans, as the steeper increase in white matter volume in adolescent boys compared with girls is related to higher levels of testosterone (Perrin, et al, 2008; see also Gur and Gur in this volume).…”
Section: 5 Neurobiological Mechanisms Underlying Hormone-dependent mentioning
confidence: 99%